Good governance via e-procurement system - Novriyanto, Novriyanto (2008)
Public procurement in government context involved complicated processes and too budget-consuming. Inadequate and not transparency information are the main factors that cause corruption and data manipulation. However, to avoid such problems, the development of web-based e-procurement system gives priority to integrity, transparency, accountability, fairness, economy, and efficiency is needed. The e-procurement system mentioned involved five main modules such as vendor management system, announcing the acquisition of good and services, electronic access to tender documents, tender submission document, and tender selection. This e-procurement system gives privileges to all of the committee members in calculating marks to determine the winners based on their committee position. Moreover, this e-procurement system can automatically alert important events such as the due date of registration, the marking date, and the date of winner announcement. By using this e-procurement system, three stakeholders can see the benefits. First, in term of government side where reducing procurement cost, transparency, time saving, access to new supplier, and blacklist vendor. Second, in term of vendor’s side where reducing cost, accessing to new buyers and increasing sales. Third, in term of public society where adequate information, and public trusts. Hopefully, good governance can be achieved by implementing this e-procurement system.